Coping mechanisms related to flood of selected families in Taal, Bocaue, Bulacan - Nario, Haydee M. (College of Home Economics, University of the Philippines Diliman, 2013)
This study aims to know the coping mechanisms related to flood of selected families in Taal, Bocaue, Bulacan. Data was gathered among 20 purposively selected families through a survey using a structured questionnaire on the different coping mechanisms before, during and after flooding. Frequency distribution and means were used to summarize and describe the data. For the extent of coping mechanism of families, an index of coping mechanism is computed by adding their scores on the list of practices employed by the families. Results showed that respondents have an extensive coping mechanism to flooding; obtaining high index scores on the physical, economic and social coping mechanisms. The respondents' long years of stay in the Barangay enabled them to develop these coping skills to deal with recurring annual flooding. Families indicated the most extensive level of coping after the flooding and the lowest during flooding. Physical coping is extensively practiced by majority of households before (65 percent) and after flooding (95 percent). Economic coping mechanisms are consistently extensively practiced by majority of the respondents by 65 percent of households before and during, and 75 percent after flooding. Social coping mechanisms are also extensively practiced by at least half of the households at all periods of flooding.